Star-like hexakis[di(ethoxycarbonyl)methano]-C60 with higher electron mobility: An unexpected electron extractor interfaced in photovoltaic perovskites. (August 2020) - Xing, Zhou; Li, Shu-Hui; Hui, Yong; Wu, Bao-Shan; Chen, Zuo-Chang; Yun, Da-Qin; Deng, Lin-Long; Zhang, Mei-Lin; Mao, Bing-Wei; Xie, Su-Yuan; Huang, Rong-Bin; Zheng, Lan-Sun
Abstract: Fullerene has been demonstrated to be one of the most efficient electron extractors in perovskite solar cells (PSCs). For feasibly preparing photovoltaic device by solution process, fullerene is normally functionalized in multiple for efficient increase of its solubility in polar solvents. However, multifunctionalization typically results in neighboring fullerene cages alienating to each other and, in principle, reduces electron mobility. Herein, we show a star-like multiadducted fullerene electron extractor, hexakis[di(ethoxycarbonyl)methano]-C60 (HEMC), which possesses a proper solubility in polar solvents as well as a close packing as revealed by crystallography. Likely due to its T h -symmetric structure with twelve ester 'tentacles' that can interact with neighboring fullerene derivatives or unsaturated Pb 2+ of perovskites, the HEMC displays efficient photovoltaic performance with a power conversion efficiency of 20%, a storage stability of 3840 h, a thermal stability of 300 h and a light-soaking stability of 240 h in the HEMC-interfaced PSCs. The present work exemplifies an unusual application of fullerene multiadducts, in addition to increasing solubility, for solving charge accumulation and recombination problems in high-efficiency PSCs. Graphical abstract: Image 1 Highlights: Symmetric HEMC with higher electron mobility acts as electron extractor for PSC. Excellent solubility of HEMC in polar solvents exhibits high operability in PSCs. Both HEMC-based MAPbI3 and mixed PSCs show ~20% PCEs with excellent stability.